Impacts of the triple global crisis on growth and poverty: The case of Yemen - Breisinger, Clemens; Diao, Xinshen; Collion, Marie-Helen; Rondot, Pierre (Wiley, 2011)
Yemen is an oil‐exporting and food‐importing country with the highest levels of poverty in the Middle East and North Africa. The impacts of the triple crisis are likely to further complicate pre‐existing conditions of conflict, oil depletion and governance failure. Using a dynamic CGE model, this article finds that oil‐driven growth in 2008 dominated the negative growth impacts of the food crisis, but that growth was not pro‐poor. The financial crisis of 2009 slowed growth sharply and raised the poverty rate to 42.8%, up from 34.8% in 2005/6. Poverty continues to be higher in rural areas, where almost half the population live in poverty.